Leaf anatomy plasticity of Acca sellowiana (O. Berg) Burret in vitro cultured in natural ventilation system and ex vitro acclimatized - Caetano, Ana Paula; Guanais, Dara Damiana Souza; Guerra, Miguel Pedro; Fermino Junior, Paulo Cesar Poeta (Plant Cell Culture & Micropropagation - ISSN 1808-9909, 2021)
Acca sellowiana (Berg) Burret is a fruit species native to southern Brazil and Uruguay. Micropropagation techniques have been developed in order to scale-up the mass propagation of new varieties. Micropropagated plants display anatomical, morphological and physiological changes, which may negativelly affect their initial development in the acclimatization phase. The objective of this work was to compare morphometric characteristics of leaf tissues in vitro culture system with natural and conventional ventilation, as well as during in vitro culture and the acclimatization phase. Stomatal density, stomatal length, pore length and chlorophyll contente were enhanced in the natural ventilation system. The stomatal density, xylem area perimeter, mesophyll, palisade and spongy parenchyma showed plasticity indicating greater adaptability in water and light relationships in the transition from in vitro to ex vitro culture. Index terms: Feijoa; gas exchange; micropropagation; leaf histology; stomata.